Biochemical Diagnosis of Coenzyme Q(10) Deficiency - Yubero, Delia (S. Karger AG, 2014)
Coenzyme Q(10) (CoQ(10)) deficiency appears to have a particularly heterogeneous clinical presentation. However, there appear to be 5 recognisable clinical phenotypes: encephalomyopathy, severe infantile multisystemic disease, nephropathy, cerebellar ataxia, and isolated myopathy. However, although useful, clinical symptoms alone are insufficient for the definitive diagnosis of CoQ(10) deficiency which relies upon biochemical assessment of tissue CoQ(10) status. In this article, we review the biochemical methods used in the diagnosis of human CoQ(10) deficiency and indicate the most appropriate tissues for this evaluation.